Graphics design work: product / Pengiran Mohamad Sufi Mohd Ain - Mohd Ain, Pengiran Mohamad Sufi (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Purnama Taste's stellar dish, Mee Pok attends to improve its recognition through a comprehensive revitalization effort. Targeted advertising, dynamic multimedia, and innovative marketing aim to propel Mee Pok to its deserved market standing, will be appealing not only to locals but also tourists. With its exceptional taste, Mee Pok offers a unique experience that beckons tourists to savor not just a dish but a culinary and cultural treasure. Redefining Purnama Taste’s Mee Pok as a must-try delight will prepare locals and visitors on a sensory journey that transcends flavours.